Transmission network expansion planning considering uncertainty in generation and demand - Escobar Z, Antonio H.; Romero, Rubén A. [UNESP]; Gallego R, Ramón A. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper presents a mathematical model and a methodology to solve a transmission network expansion planning problem considering uncertainty in demand and generation. The methodology used to solve the problem, finds the optimal transmission network expansion plan that allows the power system to operate adequately in an environment with uncertainty. The model presented results in an optimization problem that is solved using a specialized genetic algorithm. The results obtained for known systems from the literature show that cheaper plans can be found satisfying the uncertainty in demand and generation. ©2008 IEEE.
Keywords: DC model; Expansion planning; Genetic algorithm; Long-term; Optimization; Transmission network; Uncertainty in demand; Uncertainty in generation; Electric network topology; Electric power transmission networks; Genetic algorithms; Mathematical models; Problem solving